Oxidation of cassava starch with ozone and hydrogen peroxide: effect on some functional properties - Menegol, Tania (2013)
INTRODUCTION AND OBJECTIVES: Modified starches are obtained by the treatment of starch suspensions with an oxidizing agent to convert hydroxyl groups to carbonyl groups and carboxyl groups, providing starch with interesting properties in the field of food manufacturing, such as neutral taste, adhesion to surfaces, low viscosity binding, transparency gels and low tendency to retrogradation. Different oxidizing treatments have been applied to obtain cassava starch with good expansion properties. In the present study, the changes that occurred in cassava starch subjected to ozone/hydrogen peroxide and the effect of oxidation on the functional properties and expansion of modified starch with the objective of get through this treatment, starches free of metal waste and with favorable expansion properties, clarity and low viscosity are of particular interest in food applications. METHODS: To study the effect of the independent variables, i.e. ozone dosage (1, 3 and 5 g) and hydrogen peroxide content (0.25, 0.5 and 0.75%), on the amylose content, specific volume of biscuits, sum of carbonyl and carboxyl groups, paste viscosity nd intrinsic viscosity, we used the method of experimental research following a 22 composite rotational design with four axial testing conditions, four factorial trials and two repetitions at the central point, for a total of eleven randomized trials. MAIN RESULTS: The modified starches showed different properties compared to the native starch, as evidenced mainly by greater reducing power and swelling. Chemical oxidation was evidenced by an increase in the carbonyl content, as well as reduced solubility and intrinsic viscosity of amylose. DISCUSSION AND CONCLUSION: The observed differences in the physicochemical properties of native starch and modified starches using experimental research design were attributed to the differences are more specific material evaluated in this experiment, since oxidation occurred mainly in amorphous starch granules. The comparative analysis between the modified starches and native starch showed that chemical oxidation increased the content of carbonyl and carboxyl groups, increased solubility and reduced the intrinsic viscosity of amylose and decreased swelling. However, the paste viscosity and the gelation temperature were higher in the oxidized starches compared to the native starch. This was evidenced by the expansion property increase nd the specific volume of biscuits when compared to the standard. Response surface analysis showed that the combination of ozone and hydrogen peroxide had an antagonistic effect and only ozone influenced the functional properties of starch.